Development of giant Malaysian prawn (Macrobrachium rosenbergii) culture in Malaysia - Ong, Kah Sin (Malaysian Fisheries Society, 2016)
The early development of freshwater fish culture in Malaysia was confined to the culture of exotic fish species, in particular the Chinese major carps, and later also the Indian major craps and the Indonesian carp, lampam jawa (Puntius gonionotus). As these species did not gain wide popularity in the country, research was initiated to ascertain the possibility of culturing the very popular and high-value local prawn species, Macrobrachium rosenbergii, known locally as udang galah. The pioneering work conducted at the Fisheries Laboratory of the Fisheries Department Ministry of Agriculture Malaysia located at Gelugor, Penang, yielded the first success in the larval culture of the giant Malaysia prawn under laboratory conditions (Ling and Merican 1961). News of this first breakthrough generated widespread interest, and shortly thereafter, research centres from many countries initiated their own research on this prawn, with broodstock acquired in most cases from Malaysia. Thoughout the sixties, research on udang galah larviculture was gradually scaled up from glass aquaria to rectangular concrete thoughs, but the production of stockable juveniles was still limited. By the 70s, the Fisheries Research Institute had designed and built medium-scale hatcheries at both Gelugor and other localities to increase juvenile production to meet increasing demands. These were semi-enclosed hatcheries, using mostly fibreglass tanks as well as larger concrete tanks. At the same time, the Department of Fisheries developed training programmes for farmers and others interested in juvenile production. In the 80's, with technical assistance from France and Japan, the DOF was able to adopt the fully-enclosed and more intensive hatchery system and also conduct more effective training programme in both hatchery and pond culture techniques. With the encouragement and technical support from the DOF, the private sector had since then started to embark on the commercial scale development of aquaculture including the setting up of udang galah hatcheries and intensive monoculture systems.